2011
DOI: 10.1118/1.3567508
|View full text |Cite
|
Sign up to set email alerts
|

Crescent artifacts in cone‐beam CT

Abstract: Small deviations from an ideal geometry can result in crescent artifacts due to steep gradients in the bowtie filter. Angle-dependent blank projections can largely alleviate the artifacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…It was reported that BCA were induced by translational position variation of either the BF or the radiation source (15),(16) . Similar to those studies, translational position variation of the BF during gantry rotation and its repeatability were investigated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that BCA were induced by translational position variation of either the BF or the radiation source (15),(16) . Similar to those studies, translational position variation of the BF during gantry rotation and its repeatability were investigated.…”
Section: Methodsmentioning
confidence: 99%
“…We applied the two previously proposed BCA correction strategies (15),(16) in our clinical CBCT system. Strategy A used a model to predict the BF position shift, and applied the shift for each gantry angle with an in-air BF projection to correct for the BF position variation (15) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a typical clinical CBCT system for radiotherapy scatter-to-primary ratio (SPR) may even exceed 100% (Siewerdsen and Jaffray, 2001), although many methods have been proposed to correct scatter artifacts (Siewerdsen et al, 2006;Rinkel et al, 2007;Maltz et al, 2008;Zhu et al, 2009b;Poludniowski et al, 2009;Yan et al, 2010;Meyer et al, 2010;Sun et al, 2011), it is still an open problem. Third, the gantry 35 mounted bowtie filter in CBCT system may wobble, as the gantry rotates, which can result in crescent artifacts (Giles et al, 2011;Zheng et al, 2011). Moreover, there are also other factors that contribute to the intensity inconsistency between CT and CBCT, e.g.…”
Section: Introductionmentioning
confidence: 99%